Prevalence of climacteric symptoms comparing perimenopausal and postmenopausal Chinese women. (3rd July 2017) - Ruan, Xiangyan; Cui, Yamei; Du, Juan; Jin, Fengyu; Mueck, Alfred Otto
Abstract: Introduction: The climacteric symptoms during peri- and postmenopause have not been extensively studied in China. To further understanding of the characteristics of Chinese women during their menopausal transition, the aim of the study was to compare the prevalence and severity of climacteric symptoms of peri- and postmenopausal Chinese women. Methods: The retrospective descriptive study was carried out in perimenopausal and postmenopausal women from 20 provinces of China who visited Beijing Obstetrics & Gynecology hospital during 2008–2015. A total of 1225 women aged 34–76 years without hormone replacement therapy were analyzed. Menopausal status was defined by the "2011 Stages of Reproductive Aging Workshop criteria". The following climacteric symptoms were assessed: fatigue, insomnia, irritability, depression, palpitations, muscle and joint pain, dizziness, vaginal dryness, headache, urinary incontinence, hot flash, sweat, pain during intercourse, and formication. Results: The most frequent five symptoms were fatigue (75.84%), insomnia (69.39%), irritability (67.02%), palpitations (62.78%), and depression (61.88%). The prevalence of 14 symptoms was significantly higher in the postmenopause compared with the perimenopause status group (all p  < .05).The severity of fatigue, insomnia, irritability, palpitation, vaginal dryness, muscle, and joint pain and pain during intercourse was significantly different between the perimenopausal and postmenopausal groups. Conclusions: The most frequent five symptoms among the investigated 1225 Chinese women were fatigue, insomnia, irritability, palpitations, depression, nearly the same in perimenopausal and postmenopausal women. The prevalence and the severity of most of the symptoms were significantly different between the two groups.